Reproduction performance of climbing perch Anabas testudineus F1 and F2 broodstock with different dietary supplementation - Helmizuryani, Helmizuryani; Boby Muslimin; Khusnul Khotimah (Jurnal Akuakultur Indonesia)
ABSTRACT